Effects of motion and structural vibration–induced loadings on the coupled dynamic response of a mono-column tension-leg-platform floating wind turbine. (May 2020) - Imani, Hasan; Abbaspour, Madjid; Tabeshpour, Mohammad Reza; Karimirad, Madjid
Floating wind turbines are subjected to highly dynamic and complicated environmental conditions leading to significant platform motions and structural vibrations during operation and survival conditions. These motions and vibrations alter the induced loading characteristics; and consequently, affect the dynamic behavior of the system. In order to better understand the influence of such motions and structural vibrations, herein elastic structural disturbance of tower, on the system behavior, the spectral and statistical characteristics of a floating wind turbine dynamic responses under operational and survival conditions are fully explored using a fully coupled aero-hydro-servo-multi-rigid-flexible-body model. The spectral comparison results showed the important role of aerodynamic damping in reducing the high-frequency resonant responses in operational conditions. These analyses also revealed the effects of tower elasticity in shifting and amplifying high-frequency resonant responses. The statistical comparison results showed that the mean values of the responses are dominated by wind loads and the maximum and standard deviations of the responses are mainly induced by the combination of support platform motions and wave loads. It was also shown that elastic structural deformation of tower enlarges the statistical characteristics of the responses, especially when the system is subjected to both wind and wave loadings.